2016
DOI: 10.1037/emo0000188
|View full text |Cite
|
Sign up to set email alerts
|

A flexible influence of affective feelings on creative and analytic performance.

Abstract: Considerable research shows that positive affect improves performance on creative tasks and negative affect improves performance on analytic tasks. The present research entertained the idea that affective feelings have flexible, rather than fixed, effects on cognitive performance. Consistent with the idea that positive and negative affect signal the value of accessible processing inclinations, the influence of affective feelings on performance on analytic or creative tasks was found to be flexibly responsive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 65 publications
(113 reference statements)
3
24
0
Order By: Relevance
“…In a second study, the same pattern of flexibility was observed for performance on a remote associates task and insight problems (Huntsinger & Ray, ; Experiment 2). Because these tasks have objectively correct answers, differences in the number of correct answers reflect differences in qualitative aspects of creativity.…”
Section: Evidencesupporting
confidence: 55%
See 4 more Smart Citations
“…In a second study, the same pattern of flexibility was observed for performance on a remote associates task and insight problems (Huntsinger & Ray, ; Experiment 2). Because these tasks have objectively correct answers, differences in the number of correct answers reflect differences in qualitative aspects of creativity.…”
Section: Evidencesupporting
confidence: 55%
“…No effect of affective feelings on quantitative performance was found (e.g., number of uses generated), which is consistent with past research that manipulated attentional orientation (Friedman, Fishbach, Förster, & Werth, ). Thus, this research provides evidence for a flexible link between affect and cognitive processing styles, independent of the effort put into a task (for a further discussion of this distinction, see Huntsinger & Ray, ).…”
Section: Evidencementioning
confidence: 68%
See 3 more Smart Citations